BI 44370 TA, an oral CGRP antagonist for the treatment of acute migraine attacks: Results from a phase II study - Hans‐Christoph Diener; Piero Barbanti; Carl Dahlöf; Uwe Reuter; Julia Habeck; Jana Podhorná (2010)
Methods: Four hundred and sixty-one adult subjects with migraine were randomised to one of five treatments, the oral antagonist at the calcitonin gene-related peptide (CGRP) receptor BI 44370 TA (50 mg, 200 mg, 400 mg), active comparator eletriptan 40 mg or placebo. The analysis included 341 subjects who took study medication. Results: The primary endpoint, pain-free after two hours, was reached by significantly more subjects in the BI 44370 TA 400 mg (20/73 = 27.4%) and eletriptan 40 mg (24/69 = 34.8%) groups compared to placebo (6/70 = 8.6%, p = .0016), but not by subjects in the BI 44370 TA 200 mg group (14/65 = 21.5%). The effect of 50 mg BI 44370 TA (5/64 = 7.8%) was similar to that of placebo. Analysis of secondary endpoints supported the conclusion from the primary analysis. The frequency of adverse events was low in all groups. Conclusion: Efficacy of BI 44370 TA was shown in a dose-dependent manner in the treatment of acute migraine attacks.